Desert-adapted tomato Solanum pennellii exhibit unique regulatory elements and stress-ready transcriptome patterns to drought - J. Sebastián Contreras-Riquelme; Miguel Contreras; Tomás C. Moyano; Rachid Sjoberg; José Jimenez-Gomez; José M. Álvarez (PLoS ONE, 2025)
Drought is a significant environmental stressor that severely impairs plant growth and agricultural productivity. Unraveling the molecular mechanisms underlying plant responses to drought is crucial for developing crops with enhanced resilience. In this study, we investigated the transcriptomic responses of cultivated tomato (Solanum lycopersicum) and its drought-tolerant wild relative, Solanum pennellii, to identify “stress-ready” gene expression patterns associated with pre-adaptation to arid environments. Through RNA-seq analysis, we identified orthologous genes between the two species and compared their transcriptomic profiles under both control and drought conditions. Approximately 43% of the orthologous genes exhibited species-specific expression patterns, while nearly 20% were classified as stress-ready. These stress-ready genes were significantly enriched for functions related to nucleosome assembly, RNA metabolism, and transcriptional regulation. Furthermore, transcription factor binding motif analysis revealed a marked enrichment of ERF family motifs, emphasizing their role in both stress-ready and species-specific responses. Our findings indicate that regulatory mechanisms, particularly those mediated by ERF transcription factors, are pivotal to the drought resilience of S. pennellii, providing a foundation for future crop improvement strategies.